Characterization of auto-agglutinating and non-typeable uropathogenic Escherichia coli strains - Ulises Hernández-Chiñas; Alejandro Pérez-Ramos; Laura Belmont-Monroy; María E Chávez-Berrocal; Edgar González-Villalobos; Armando Navarro-Ocaña; Carlos A Eslava; Jose Molina-Lopez (Journal of Infection in Developing Countries)
Introduction: Uropathogenic Escherichia coli (UPEC) are the main etiological agent of urinary tract infections (UTIs). Association between different serotypes and UTIs is known, however, some strains are incapable to be serotyped. The aim of this work was to study bthe phenotypical and genotypical characteristics of 113 non-typeable (NT) and auto-agglutinating (AA) E. coli strains, isolated from UTIs in children and adults.